Recent progress in metal assisted multicomponent reactions in organic synthesis - Sakthivel, Kokila; Gana, R. J.; Shoji, Toshitaka; Takenaga, Naoko; Dohi, Toshifumi; Singh, Fateh V. (Frontiers in Chemistry, 2023)
To prepare complicated organic molecules, straightforward, sustainable, and clean methodologies are urgently required. Thus, researchers are attempting to develop imaginative approaches. Metalcatalyzed multicomponent reactions (MCRs) offer optimal molecular diversity, high atomic efficiency, and energy savings in a single reaction step. These versatile protocols are often used to synthesize numerous natural compounds, heterocyclic molecules, and medications. Thus far, the majority of metal-catalyzed MCRs under investigation are based on metal catalysts such as copper and palladium; however, current research is focused on developing novel, environmentally friendly catalytic systems. In this regard, this study demonstrates the effectiveness of metal catalysts in MCRs. The aim of this study is to provide an overview of metal catalysts for safe application in MCRs.